2004
DOI: 10.1002/bjs.4792
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive fibromatosis of the abdominal wall, limbs and limb girdles

Abstract: Wide excisional, function-preserving surgery is the goal in treatment of AF. Surgery for recurrent disease is often curative. Tumours are frequently irresectable at presentation and an initial period of expectant observation is advisable because growth arrest is a common feature of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 37 publications
3
55
1
1
Order By: Relevance
“…[19][20][21][22][23][24][25] Studies in adult AF have reported functionsparing surgery as their primary objective and suggested that, to reduce the risk of major sequelae, marginal surgery may be acceptable. [26][27][28][29] Our series revealed a high local recurrence rate after incomplete surgery; however, disease control was no better in Group II than in Group III. In principle, our findings suggest that primary surgery should only be attempted if it can be complete (ie, if it can achieve histologically negative margins), and nonmutilating excisions are naturally feasible; otherwise, neoadjuvant systemic treatment should be recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25] Studies in adult AF have reported functionsparing surgery as their primary objective and suggested that, to reduce the risk of major sequelae, marginal surgery may be acceptable. [26][27][28][29] Our series revealed a high local recurrence rate after incomplete surgery; however, disease control was no better in Group II than in Group III. In principle, our findings suggest that primary surgery should only be attempted if it can be complete (ie, if it can achieve histologically negative margins), and nonmutilating excisions are naturally feasible; otherwise, neoadjuvant systemic treatment should be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Several observations from the adult literature that desmoid tumors can remain stable for a long time, with or without primary treatment, prompt the suggestion that a ''waitand-see'' approach (clinical/radiologic monitoring alone) may be suitable for patients who have nonevolving disease, and therapies should be given only in the event of tumor growth. 23,[27][28][29] Systemic treatment, and particularly low-dose chemotherapy, may play a significant role in the treatment of locally advanced disease; however, the role for adjuvant chemotherapy remains unclear. Although others have reported some benefits, 17 no useful information emerged from our series on its role for patients in Group II.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Although unable to metastasize, these highly infiltrative and locally destructive lesions have a significant tendency to recur, with recurrence rates ranging from 19 to 38% in multiple studies. 2,[11][12][13][14][15][16][17][18][19][20][21][22][23] Currently there are no reliable methods to identify those tumors with a higher risk for recurrence; the molecular determinants of desmoid behavior remain primarily unknown. 23 Surgical resection remains the mainstay of desmoid therapy; however, these tumors frequently require multiple and at times debilitating surgical interventions for their control, resulting in significant treatment-related morbidity such as amputation or loss of significant portions of foregut.…”
mentioning
confidence: 99%
“…S. Phillips и соавт. [43] привели результаты лече-ния 23 пациентов по аналогичной методике. Некоторые авторы [44][45][46][47] отмечают удовлетворительные функцио-нальные результаты при использовании сетчатых проте-зов из политетрафторэтилена (ePTFE) и целлюлярного дермального матрикса.…”
Section: Discussionunclassified